BioRegio, BioProfile and the rise of the German biotech industry - Dirk Dohse; Tanja Staehler (Kiel Institute for the World Economy (IfW), 2008)
The BioRegio contest and the BioProfile contest initiated by the German Federal Government have drawn much international attention as prototypes of a new kind of technology policy aiming at the exploitation of regional innovation and growth potential through clustering. There is, however, little systematic analysis of their actual impact on the development of commercial biotechnology in Germany. The current paper tries to fill this gap. We find that although these contests have catalyzed the emergence and early growth of German commercial biotech it takes more than isolated policy action by national governments to grow a self-sustainable biotech industry in Europe.
Keywords: R11; R38; O3; 330; Clustering; biotech; technology policy; regional development; Biotechnische Industrie; Regionale Konzentration; Biotechnische Forschung; Forschungs- und Technologiepolitik; Innovationspolitik; Regionalpolitik; Wirtschaftspolitische Wirkungsanalyse; Deutschland